Outcome and complications of self-administration of over-the-counter abortion pills: an observational study in a tertiary care hospital of a medical college in New Delhi - Singh, Anjali; Bhaskaran, Sruthi; Singla, Anshuja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Due to unrestricted free availability of abortion pills, despite of national policies, guidelines and medical termination of pregnancy (MTP) act, unsafe abortions by self-administration of these drugs for termination of unwanted pregnancies without prescription are becoming common in our country, leading to associated morbidity and mortality. Methods: A prospective Observational study was done at Guru Teg Bahadur hospital, university college of medical sciences, New Delhi, from November 2019 to April 2020, in the department of gynecology and obstetrics, on women visiting the outpatient department and casualty department with the history of self-administration of medical termination pills without prescription. This study was done to study the outcome and complications occurring due to self-administration of over-the-counter abortion pills that are freely available in the market. 95 women were included in study and data was collected regarding age, education level, parity, presenting complaints, complications and their management. Descriptive analysis of the collected data was done. Results: In this study 95 women were included 71.6% took pills before 8 weeks of gestation, 1% took in second trimester. 46.3% landed up in incomplete abortion and 33.68% needed surgical evacuation, 8.42% had ectopic out, 2.1% had scar site pregnancy and 7.36% needed laparotomy, 1.05% had rupture uterus followed by abortion pill intake while 1.05% suffered from acute kidney injury (AKI). There was no ICU admission nor any mortality. Conclusions: There is urgent need of strict legislation to curtail this bad practice and free availability of over-the-counter abortion pills which leads to unexpected morbidity and mortality, such drugs should be given only by health care providers under supervision, there is need of community level awareness so as to impart knowledge regarding this problem.